miR-655-3p targeting KIF20A inhibits migration and invasion of lung adenocarcinoma cell line A549 - DU Xue-mei, ZHANG Yun-mei, ZHOU Wen-ting, LYU Hong (Jichu yixue yu linchuang, 2022)
Objective To investigate the effects of miR-655-3p targeting kinesin family member 20A (KIF20A) on cell proliferation, migration and invasion of lung adenocarcinoma cells. Methods RT-qPCR was used to detect the expression of miR-655-3p in human lung adenocarcinoma cell lines H460, A549, HCC-2935, and H1299. A549 cells at logarithmic proliferation stage were divided into: blank group, miR-NC group, miR-655-3p mimics group, si-NC group, si-KIF20A group, miR-655-3p mimics+OE-NC group, miR-655-3p mimics+OE-KIF20A group. RT-qPCR was used to detect the miR-655-3p expression. Western blot was used to detect the KIF20A, matrix metalloproteinase 2 (MMP-2), MMP-9,RAS/mitogen-activated protein kinas (MAPK) pathway related protein expression; CCK-8 was used to detect cell proliferation; transwell experiment was used to detect cell migration and inva-sion; dual luciferase reporter gene detection experiment was used to verify the targeting relationship between miR-655-3p and KIF20A. Results miR-655-3p was less expressed in human lung adenocarcinoma cell lines, and has the lowest expression in A549 cells. Over-expression of miR-655-3p or silencing KIF20A inhibited A549 cell proliferation, migration, invasion and MMP-2, MMP-9, phosphorylation extracellular regulatory protein kinase 1/2(p-ERK1/2), phosphoinositide 3-kinase (p-PI3K) and phosphorylated protein kinase B (p-AKT) protein expression (P＜0.05). The miR-655-3p targeted at and negatively regulated the expression of KIF20A. Up-regulation of KIF20A inhibited the effects of over-expression of miR-655-3p on the proliferation, migration, invasion and RAS/MAPK pathway related proteins of A549 cells. Conclusions Over-expression of miR-655-3p may down-regulate KIF20A and inhibit the proliferation, migration and invasion of lung adenocarcinoma cells. This mechanism may be related to the inhibition of the RAS/MAPK pathway.